The Urgence of Establishing Online Dispute Resolution (Odr) as A Dispute Resolution of Information Technology-Based Lending and Lending Services - Conie Pania Putri; Bahrul Ilmi Yakup; Husni Thamrin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The urgency of establishing an online dispute resolution (ODR) as an effort to resolve disputes over information technology-based lending and borrowing services is based on the background that borrowers often fail to pay which causes losses to lenders. However, in practice, lenders cannot take legal action and accept losses which are known as the risk of default. Therefore, it is necessary to establish an Online Dispute Resolution (ODR) as a solution to solve these problems.The writing of this paper uses a normative juridical method with a statutory approach. This study uses primary, secondary, and tertiary legal materials which are analyzed qualitatively according to their relevance to research problems which are then presented in the form of exploratory and argumentative descriptive narratives.From the results of the research using the above method, the authors obtain answers to the existing problems that technology-based dispute resolution for lending and borrowing money services can be resolved through alternative dispute resolution using the Online Dispute Resolution (ODR) model.